PENERAPAN BRAIN BASED LEARNING (BBL) BERBANTU GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMP MATERI BANGUN DATAR - Melva Sitorus; Hafsah Adha Diana (Jurnal Karya Pendidikan Matematika, 2022)
The ability of mathematical connections is needed by students, because mathematics is a unit, where mathematics material is related and related to other sciences. The purpose of this study is to improve students' mathematical connection skills through the application of geogebra-assisted brain based learning (BBL) on geometry transformation material. This research method is experimental research. This type of research is qualitative research. The population in this study were all students of SMP 253 Jakarta Class VIII for the academic year 2021/2022. The sample of this study consisted of one class VIII which was selected using random sampling technique. The instruments used in the study were tests, interviews and observations. The analytical technique used in this research is descriptive analysis. Activities in the analysis in this study are data reduction (data reduction), data presentation (data display), and conclusions. The validity of the data used with this research technique there are 3 namely persistence of observation, tringulas, peer checking. Based on the results of the analysis, it can be obtained from the application of Brain Based Learning (BBL) assisted by Geogebra in improving mathematical connection skills in class VIII class VIII SMP Negeri 253 Jakarta.